COVID-19 lockdown and seasonal allergic rhinitis: our experience in 40 patients - Gelardi, Matteo; Trecca, Eleonora; Fortunato, Francesca; Iannuzzi, Lucia; Ronca, Gianluca; Quaranta, Nicola; Cassano, Michele (Acta Biomedica Atenei Parmensis, 2021)
Introduction: The aim of this article was to study the course of seasonal allergic rhinitis during COVID-19 lockdown in order to understand if being quarantined at home for a long time can constitute a protective factor for allergic patients. Materials and methods: Telehealth consultations were performed by the departments of Otolaryngology of Foggia and Bari University Hospitals. Participants took part in a phone interview and were asked about their sinonasal symptoms during the COVID-19 lockdown, by answering the sinonasal outcome test (I-SNOT-22) questionnaire. Further data concerning the medications used to treat allergy and the number of days per month in which they were used were collected. The responses about the COVID-19 lockdown were compared to those obtained by the same patients in our clinics the previous year. The statistical analysis was executed by using the paired sample t-test and the Bartlett test considering as significant values with p values <0.05. Results: Forty patients affected by cypress pollen allergy visited at Foggia and Bari University Hospitals were enrolled in this study. All I-SNOT-22 scores concerning the COVID-19 lockdown were lower than those of the previous year; moreover, 18 (81.8%) clinical parameters were statistically significant (p<0.05). Also, in regard to the treatment, results about COVID-19 lockdown were overall better than those of 2019, with 50% (n=3) of the investigated drugs, reporting statistical significance (p<0.05). Conclusions: The present study was able to evidence the fundamental role of primary prevention in Allergology. Paradoxically, the home quarantine ordered by the Italian Government appeared to be an effective measure not only in the fight against COVID-19 but also against pollen exposure.